(untitled) (REMUNOM, 2025)
Over the years, society has experienced technological innovations that have transformed several sectors, including public management. This accelerated advancement of the digital age and the incorporation of emerging technologies in the government sphere has become essential to the objective of promoting significant changes that could bring effective results to the public sector. Given this scenario and the need to undergo a process of digital transformation, this article identifies the main technologies adopted in the Brazilian public sector and analyzes the transformative impact of the adoption of these technologies, highlighting how they are driving innovation and catalyzing the era of digital transformation in the public sphere. To achieve the proposed objective, a qualitative methodology was used with a narrative analysis of the literature, referring to digital transformation and interventions in the implementation of technologies in the Brazilian public service. The theoretical analysis showed that the use of technologies enhances the promotion of more efficient public management, significantly impacts government processes, the provision of public services and decision-making. This research aims to contribute to the development of existing knowledge and offer relevant insights for understanding the impact of digital technologies on the Brazilian public sector.